PENGARUH STORE IMAGE, VALUE CONSCIOUSNESS, PRICE IMAGE DAN ATTITUDE TOWARD PRIVATE BRAND PADA CONSUMER PURCHASE INTENTION di ALFAMART SURABAYA TIMUR - Setiawan, Adi (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This study aimed to determine the effect of store image, value consciousness, price image, attitude toward private brand for consumer purchase intention Alfamart in East Surabaya. The research was conducted by distributing the questionnaires as the primary data directly on site. The samples in this research were 100 people, which then analyzed using linear regression to determine the effect between the variable through the SPSS 13 program. The results of this study showed that the store image, value consciousness, price and image, attitude toward private brand in Alfamart that offered in East Surabaya are able to have a positive influence on purchase intention of consumers who shops in Alfamart of East Surabaya.